Utilizing the Environment as a Learning Medium to Improve Science Learning Outcomes: Pemanfaatan Lingkungan sebagai Media Pembelajaran untuk Meningkatkan Hasil belajaran IPA - Rohmiati (Institute of Educational, Research, and Community Service, 2023)
This research aims to investigate the effectiveness of utilizing the environment as a learning medium to enhance the learning outcomes of Science (IPA) among fifth-grade students at SDN 3 Rumbuk in the academic year 2022/2023. The research was conducted in two action research cycles to observe the changes that occurred alongside the implementation of environmental utilization as a learning medium. The participants in this research were 21 fifth-grade students at SDN 3 Rumbuk. This classroom action research was conducted with several stages, namely planning, action, observation, and reflection. Each action cycle consisted of these stages, designed to plan and implement learning activities by utilizing the surrounding environment as a medium for IPA learning. The data collected in this research included test results, classroom observations, field notes, and teacher reflections. Tests were used to measure students' learning outcomes in understanding IPA concepts taught through the utilization of the environment as a learning medium. Classroom observations and field notes were used to observe student-teacher interactions and the effectiveness of using the environment as a learning medium. Teacher reflections were used to evaluate the success of each action cycle and determine the changes or adjustments that needed to be made. The results of the research indicate that the utilization of the environment as a learning medium has a positive impact on students' IPA learning outcomes. There was a significant improvement in students' understanding of IPA concepts from one action cycle to the next. Students also demonstrated more active engagement and enthusiasm in the learning process when the surrounding environment was used as a learning medium